2020
DOI: 10.1101/2020.06.08.20124792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serological Assays Estimate Highly Variable SARS-CoV-2 Neutralizing Antibody Activity in Recovered COVID19 Patients

Abstract: Background: The development of neutralizing antibodies (NAbs) against SARS-CoV-2, following infection or vaccination, is likely to be critical for the development of sufficient population immunity to drive cessation of the COVID19 pandemic. A large number of serologic tests, platforms and methodologies are being employed to determine seroprevalence in populations to select convalescent plasmas for therapeutic trials, and to guide policies about reopening. However, these tests have substantially variable sensit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 31 publications
6
64
1
Order By: Relevance
“…The latter approximation would be similar to the Santa Clara seroprevalence rate reported in April of 2020, which found a seroprevalence rate of 2.5-4.2% using LFA assays. (16) However, since the IgM LFA assay correlated poorly with the Ortho HTSA assay, which we have previously shown to associate with neutralization activity and antiviral antibody effectiveness to prevent reinfection of cells with pseudovirus , (14) we conclude the SD Biosensor IgM LFA assay may not be informative as to an adaptive immune response to SARS-CoV-2. It should be noted that a concurrent SARS-CoV-2 serology study comparing the SD Biosensor LFAs to another LFA and a chemiluminescent assay concluded that the SD Biosensor IgM LFA had limited clinical utility, while the SD Biosensor IgG LFA performed very well across several distinct population sets and compared to the other assays.…”
Section: Discussionmentioning
confidence: 82%
“…The latter approximation would be similar to the Santa Clara seroprevalence rate reported in April of 2020, which found a seroprevalence rate of 2.5-4.2% using LFA assays. (16) However, since the IgM LFA assay correlated poorly with the Ortho HTSA assay, which we have previously shown to associate with neutralization activity and antiviral antibody effectiveness to prevent reinfection of cells with pseudovirus , (14) we conclude the SD Biosensor IgM LFA assay may not be informative as to an adaptive immune response to SARS-CoV-2. It should be noted that a concurrent SARS-CoV-2 serology study comparing the SD Biosensor LFAs to another LFA and a chemiluminescent assay concluded that the SD Biosensor IgM LFA had limited clinical utility, while the SD Biosensor IgG LFA performed very well across several distinct population sets and compared to the other assays.…”
Section: Discussionmentioning
confidence: 82%
“…Comparison of the specific IgG antibody titers across studies cannot be done because of varied assay methods. Epidemiological studies have reported that neutralizing antibody titers vary widely in convalescent serum samples and may be related to several factors (eg, age, sex, disease severity, and days since infection), [13][14][15][16][17][18] but none of those studies used the PRNT method. In addition, some studies have indicated that the antibody titers may decline over time in patients recovered from COVID-19, [19][20][21] particularly in those who were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…S and N proteins in particular, have been the focus of several targets for serological assays on the basis that previous studies have indicated that they are the most immunogenic antigens. 8,9 Walls and colleagues have shown coronavirus S protein mediates viral entry into host cells. The S protein consists of two functional subunits namely the S1 subunit which binds to the host cell receptor and S2 subunit which leads to fusion of viral and cellular membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Archived serum samples taken from patients prior to December 2019 representing COVID-19 naivety were used as negative controls. These included healthy blood donors as well as patients with and without other positive serological tests: anti-extractable nuclear antigen antibodies (9); anti-glomerular basement membrane antibodies (4); antismooth muscle antibody (3); hepatitis A IgM (3); Epstein -Barr virus IgM (3); anti-intrinsic factor IgG (5); cytomegalovirus IgM (4); cytomegalovirus IgG (3); syphillis treponemal antibody (5); Epstein -Barr virus IgA (7); Leptospira IgM (3); hepatitis C antibody (9); hepatitis B surface antigen (7); hepatitis B e antigen (2); anti-double stranded DNA IgG (3); rubella IgM (4); antinuclear antibodies (3); hepatitis A IgG (3); dengue virus IgG (1); varicella zoster IgM (1); human immunodeficiency virus (8); and varicella zoster virus IgG (6). Prior to testing patients' sera, calibration was performed and quality controls were passed as per manufacturers' instructions.…”
Section: Methodsmentioning
confidence: 99%